Spatiotemporal neural dynamics of moral judgment: A high-density ERP study - Yoder, Keith J.; Decety, Jean (Neuropsychologia, 2014)
Morality is a pervasive aspect of human nature across all cultures, and neuroscience investigations are necessary for identifying what computational mechanisms underpin moral cognition. The current study used high-density ERPs to examine how moral evaluations are mediated by automatic and controlled processes as well as how quickly information and causal-intentional representations can be extracted when viewing morally laden behavior. The study also explored the extent to which individual dispositions in affective and cognitive empathy as well as justice sensitivity influence the encoding of moral valence when healthy participants make moral judgments about prosocial (interpersonal assistance) and antisocial (interpersonal harm) actions. Moral judgment differences were reflected in differential amplitudes for components associated with cognitive appraisal (LPP) as well as early components associated with emotional salience (N1 and N2). Moreover, source estimation was performed to indicate potential neural generators. A posterior-to-anterior shift was observed, with current density peaks first in right inferior parietal cortex (at the temporoparietal junction), then later in medial prefrontal cortex. Cognitive empathy scores predicted behavioral ratings of blame as well as differential amplitudes in LPP and component activity at posterior sites. Overall, this study offers important insights into the temporal unfolding of moral evaluations, including when in time individual differences in empathy influence neural encoding of moral valence. •Moral valence is encoded rapidly (<300ms) and influences both N1 and N2 components.•During moral judgment, neural recruitment shifts from TPJ to medial prefrontal cortex.•Affective and causal-intentional representations support extraction of moral content.•Prosocial actions are processed as more pleasant and rewarding than antisocial ones.•Dispositional differences in cognitive empathy predict LPP amplitude differences.